Healthy Lifestyle, Distress and Eustress in Adolescents - Bahtiar, Alda Nur; Syakarofath, Nandy Agustin (Universitas Brawijaya, 2026)
Adolescence is an important transition phase that is prone to experiencing stress, both negative (distress) and positive (eustress). One of the protective factors to be able to manage the stress felt is to implement a healthy lifestyle. The purpose of this research is to test the role of a healthy lifestyle in predicting distress and eustress in adolescents. The design of this study is quantitative correlational. The participants who were actively involved in this study were 139 adolescents aged 15–18 years who were obtained using accidental sampling techniques. The instruments used in the data collection process were the Adolescent Healthy Lifestyle Questionnaire (AHLQ) and the Adolescent Distress-Eustress Scale (ADES). Based on regression analysis, it was shown that a healthy lifestyle was able to predict the stress experienced by adolescents. This means that a healthy lifestyle has a significant negative relationship with distress and has a significant positive influence on eustress. The data from the aspect analysis also enriched the findings of this study by explaining that life appreciation and social support are the aspects of a healthy lifestyle that contribute the most significant compared to health responsibilities, diet, physical activity, and stress management. These findings imply that mental health interventions for adolescents should pivot toward holistic lifestyle programs that centrally incorporate life appreciation practices and health responsibility as the most consistent predictors to effectively buffer against distress and foster positive psychological growth. Masa remaja adalah fase transisi penting yang rentan mengalami stres, baik negatif (kesusahan) maupun positif (eustress). Salah satu faktor pelindung untuk dapat mengelola stres yang dirasakan adalah dengan menerapkan pola hidup sehat. Tujuan dari penelitian ini adalah untuk menguji peran gaya hidup sehat dalam memprediksi kesusahan dan eustress pada remaja. Desain penelitian ini bersifat korelasi kuantitatif. Peserta yang terlibat aktif dalam penelitian ini adalah 139 remaja berusia 15-18 tahun yang diperoleh dengan menggunakan teknik accidental sampling. Instrumen yang digunakan dalam proses pengumpulan data adalah Kuesioner Gaya Hidup Sehat Remaja (AHLQ) dan Skala Tekanan Remaja (ADES). Berdasarkan analisis regresi, ditunjukkan bahwa pola hidup sehat mampu memprediksi stres yang dialami remaja. Ini berarti bahwa gaya hidup sehat memiliki hubungan negatif yang signifikan dengan kesusahan dan memiliki pengaruh positif yang signifikan pada eustress. Data dari analisis aspek juga memperkaya temuan penelitian ini dengan menjelaskan bahwa apresiasi hidup dan dukungan sosial merupakan aspek gaya hidup sehat yang berkontribusi paling signifikan dibandingkan dengan tanggung jawab kesehatan, pola makan, aktivitas fisik dan manajemen stres. Temuan ini mengimplikasikan bahwa intervensi kesehatan mental bagi remaja perlu beralih ke program gaya hidup holistik yang secara kuat mengintegrasikan praktik apresiasi kehidupan dan tanggung jawab kesehatan sebagai prediktor yang paling konsisten guna meredam distres secara efektif sekaligus mendorong pertumbuhan psikologis yang positif.